CT imaging characteristics of nontuberculous mycobacteria lung disease, active tuberculosis and multi-drug resistant tuberculosis - Xu, Liang; Xu, Shuangmei (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background: The differential diagnosis of nontuberculous mycobacteria (NTM) lung disease, active tuberculosis (ATB) and multi-drug resistant tuberculosis (MDR-TB) remains difficult. Objectives: To explore the CT imaging characteristics of NTM lung disease, ATB and MDR-TB for differential diagnosis. Methods: Patients with NTM lung disease (n=98), ATB (n=98) and MDR-TB (n=98) who were examined and treated from August 2015 to May 2019 were included. Their chest CT imaging results were retrospectively analyzed, and the imaging characteristics were compared. Results: The proportion of cases complicated with underlying lung disease, cough and hemoptysis was significantly higher in NTM group than those in ATB and MDR-TB groups (P<0.05). Compared with ATB and MDR-TB groups, NTM group had significantly more cases of nodule-bronchus dilation type, but significantly fewer cases of nodule-mass type and other types (P<0.05). In NTM group, the cases of thin-wall cavity, bronchiectasis and centrilobular nodules increased, but the detection rate of thick-wall cavity, lung consolidation, atelectasis, lung damage, lung volume reduction, intrapulmonary calcification, hilar and mediastinal lymph node calcification, acinar nodules, pleural thickening and pleural effusion declined compared with ATB and MDR-TB groups (P<0.05). The detection rates of lesions, cavities and bronchiectasis in the lingual lobe of left lung and middle lobe of right lung were significantly higher in NTM group than those in ATB and MDR-TB groups (P<0.05). Conclusions: The imaging characteristics of NTM lung disease are quite similar to those of ATB and MDR-TB, but they can be differentially diagnosed through the types of cavities and nodules, incidence rate of bronchiectasis, and differences in lung consolidation, lung damage, calcification, pleural thickening and pleural effusion.